Users’ Mental Model Pattern for User Interface Design of Mobile Shopping Apps - Punitha Turumugon; Aslina Baharum; Rozita Hanapi; Nurfaizah Kamarudin; Emelia Abdul Rahim; Muhammad Omar (American Scientific Publishers, 2018)
In recent years the emergence of smartphones has changed the definition of mobile phones. It has become an essential part of the peoples’ communication and daily life. Mobile apps have become more popular nowadays with the emergence of smartphones. Mobile app is application software designed to run on perspicacious phones and tablet computers. Shopping apps are now the fastest growing apps among mobile apps. Mobile user interface design (UID) is an essential in the mobile apps development process. A poor user interaction in mobile apps could lead to failure of an app. The used of mental model theory could help the mobile apps developers to design a greater user interface (UI). This study discussed on how mental model theory implemented in interface design practices for a mobile shopping app development. Mental model theory using ‘Localization’ and content analysis method will be used throughout this research study. The expected output of this research is to develop a fast, user-friendly and strong visual hierarchy interface guideline for a UID of mobile shopping apps. According to this study, different gender had a different mental model on the user interface for a mobile shopping app.